Chemical Composition of Leaf and Seed Oils of Dryobalanops aromatica Gaertn. (Dipterocarpaceae) - A.S Kamariyah; T Ozek; B Demirci; K.H.C. Baser (ASEAN Journal on Science and Technology for Development, 2012)
The essential oils of the leaves and seed of Dryobalanops aromatica Gaertn. obtained by hydrodistillation resulted in 0.07% and 1.89% yield, respectively. These oils were then examined by GC-MS. Eighty-three components (plus an unknown) were identified from the leaf oil, representing 92% of the oil. Oxygenated monocyclic monoterpenes (terpinen-4-ol 15%, ?-terpineol 16%), bicyclic monoterpene (?-pinene 7%) and oxygenated bicyclic sesquiterpene (globulol 8%) were the major constituents. In the case of the seed oil, 31 components were identified, representing 100% of the oil, while acyclic monoterpene (myrcene 5%), monocyclic monoterpene (limonene 6%), bicyclic monoterpenes (?-pinene 41%, ?-thujene and b-pinene 13% each, sabinene 6%), and bicyclic sesquiterpene (bicyclogermacrene 6%) made up the major components. The remaining constituents of each oil (54% and 10%, respectively) were found to be minor (?4% each). The chemical compositions of both oils differed quantitatively but showed important qualitative similarities and differences. The results of this study serve as the first report of complete chemical profiles of both oils.